If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(x + 8) = 72 Reorder the terms: (2 + x)(x + 8) = 72 Reorder the terms: (2 + x)(8 + x) = 72 Multiply (2 + x) * (8 + x) (2(8 + x) + x(8 + x)) = 72 ((8 * 2 + x * 2) + x(8 + x)) = 72 ((16 + 2x) + x(8 + x)) = 72 (16 + 2x + (8 * x + x * x)) = 72 (16 + 2x + (8x + x2)) = 72 Combine like terms: 2x + 8x = 10x (16 + 10x + x2) = 72 Solving 16 + 10x + x2 = 72 Solving for variable 'x'. Reorder the terms: 16 + -72 + 10x + x2 = 72 + -72 Combine like terms: 16 + -72 = -56 -56 + 10x + x2 = 72 + -72 Combine like terms: 72 + -72 = 0 -56 + 10x + x2 = 0 Factor a trinomial. (-14 + -1x)(4 + -1x) = 0Subproblem 1
Set the factor '(-14 + -1x)' equal to zero and attempt to solve: Simplifying -14 + -1x = 0 Solving -14 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + -1x = 0 + 14 Combine like terms: -14 + 14 = 0 0 + -1x = 0 + 14 -1x = 0 + 14 Combine like terms: 0 + 14 = 14 -1x = 14 Divide each side by '-1'. x = -14 Simplifying x = -14Subproblem 2
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Solution
x = {-14, 4}
| 5s+12=0 | | (3d^4-4d^3+6)(-3c^2d)= | | 12X^3+3X^2-24X-6X=0 | | -x^2+5x=3 | | (3d^4-4d^3+6)(-3cd)= | | 4(6X-5)2= | | 6d+3d-5d-8=2d | | 9n=8n+24 | | 3x-9=2x+15 | | 5(3x-2)5= | | 3n+10=70 | | 12n-3=9 | | 76-7x=38x+21 | | (3x-4)(x-4)(x+5)= | | 3n+6=3n | | 78100-781000= | | x^2+6x-112=0 | | 14x+2y= | | (9x^2-7x+8)(8x^2+9x-7)= | | 15w-14w+12=10w | | 9x+12=3x-6 | | 58-5x=4x+17 | | 14-b=19 | | x*x-v=w*w | | -(4w+2)+2(6w-5)= | | 2x*3x^2=53-51 | | (x-3)(x-6)=4 | | 5b=21+45 | | 10+8e^3x=25 | | 2(3N-5)(3N+5)= | | 5x+1=x+1 | | 5-39=10x-17x |